2023
DOI: 10.18502/jsp.v2i2.12627
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of spine surgery research evolution in Saudi Arabia: A bibliometric analysis

Abstract: Background: Over recent decades, there has been a constant increase in the numbers and quality of spine surgery research. We herein plan to analyze the evolution of spine surgery-related publications from Saudi Arabia for three decades. Materials and Methods: A systematic review of the literature with predefined inclusion criteria was carried out, utilizing multiple significant databases (PubMed, Google Scholar, and Embase). Multiple search terms were used to retrieve related articles. Numerous variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Fourteen (47%) of the articles reviewed here were published during 2020 to 2023 [35][36][37][38][39][40][41][42][43][44][45][46][47][48], an indication that validation of Arabic versions of spine-related PROMs is an ongoing topic in the literature. Article citation numbers are known to positively correlate with journal IF and publication's age [4,13]. The relatively short duration from publication for most articles (median age four years) and low journal IF (median 2) explain the modest citation numbers (median 6.5) for the selected studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fourteen (47%) of the articles reviewed here were published during 2020 to 2023 [35][36][37][38][39][40][41][42][43][44][45][46][47][48], an indication that validation of Arabic versions of spine-related PROMs is an ongoing topic in the literature. Article citation numbers are known to positively correlate with journal IF and publication's age [4,13]. The relatively short duration from publication for most articles (median age four years) and low journal IF (median 2) explain the modest citation numbers (median 6.5) for the selected studies.…”
Section: Discussionmentioning
confidence: 96%
“…Lack of resources, absence of research infrastructure and deficiency of state-of-the-art technology were identified as the reasons why the Arab world lagged behind in biomedical research [12]. Nevertheless, an increase in academic productivity in Arab countries has been observed in the spine [11,13], and neurosurgical research in recent years [12]. The Arabic language has many different dialects, however, modern standard Arabic is widely understood and accepted in formal communication and the media in all Arab countries.…”
Section: Introductionmentioning
confidence: 99%